PENGARUH MODEL PEMBELAJARAN CTL TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VII SMP - Amelia Rahmah Adhyan; Sutirna Sutirna; Hanifah Nurus Sopiany (IKIP Siliwangi, 2022)
The purpose of this study was to see whether there were differences in the achievement and improvement of mathematical problem-solving abilities of students who received CTL learning with students who received direct learning and to see how much influence the CTL learning model had on the mathematical problem-solving abilities of experimental class students. This study uses a quantitative approach with experimental methods. The population used was class VII students at SMP Negeri 5 Karawang Barat with samples namely class VII B (experimental class applied CTL learning model) and VII D (control class applied direct learning model) taken by purposive sampling. The instruments used are test and non-test instruments (interviews), where the data obtained will be measured by statistical tests in the form of prerequisite tests, t-tests, Mann-Whitney tests (if the data are not normally distributed), n-gain and effect tests. size. The results of this study indicate that the average achievement and improvement of mathematical problem-solving abilities of students who receive CTL learning is better than students who receive direct learning, and the large influence of the CTL learning model on students' mathematical problem-solving abilities is in the criteria classified as large.